Join IDNLearn.com and become part of a knowledge-sharing community that thrives on curiosity. Get comprehensive answers to all your questions from our network of experienced experts.
Sagot :
Answer:
1
Step-by-step explanation:
for the equation of finding y is x - 5 = y
2 - 5 = -3
3 - 5 = -2
4 - 5 = -1
5 - 5 = 0
6 - 5 = 1, therefore, y is 1
Answer:
1
Step-by-step explanation:
Hope it help
Mark me as brainliest
We appreciate your presence here. Keep sharing knowledge and helping others find the answers they need. This community is the perfect place to learn together. Your questions find clarity at IDNLearn.com. Thanks for stopping by, and come back for more dependable solutions.